Interventions to promote psychiatric patients’ compliance to mental health treatment: A systematic review - Mosidi B. Serobatse; Emmerentia Du Plessis; Magdalena P. Koen (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2014)
Background: Non-compliance to treatment remains one of the greatest challenges in mental healthcare services, and how to improve this remains a problem.